What difference a 'pre' makes: University business preincubators in Germany. A national survey - Mareike Deutschmann (Leuphana Universität Lüneburg, Lehrstuhl Gründungsmanagement, 2007)
Business incubation as an instrument of fostering new venture formation is widely discussed in the research field of entrepreneurship. Numerous aspects of Business Incubators (BIs) have already been investigated in more depth: e.g. the organizational structure, funding, objectives, provided services, incubatee selection policy, impacts on the survival and growth of incubatee firms etc. So far, researchers focused their work on public-sponsored, private-sponsored, and nonprofit-sponsored BIs as well as on university-related BIs. In the case of University Business Incubators (UBIs) research basically circulated around the question of how UBIs can support technology transfer. This paper focuses on a new type of UBI: the University Business Pre-Incubator (UPI). UPIs are facilities that support embryonic businesses during their planning stage by providing office space, consultancy and training, and mentoring services. In the scope of a comprehensive support program of the German government called 'EXIST - Existenzgruendungen aus der Wissenschaft' that started in 1998, a couple of German universities established pre-incubators to assist the development of new enterprises. So despite the lack of research literature concerning business-related pre-incubators, in practice, these institutions play an important role for German universities in fostering new ventures. This paper tries to make a substantial contribution to reduce the knowledge gap in the research area of UPIs. After defining the facility 'University Business Pre-Incubator' based on metaphorical considerations and the business incubation literature, the paper presents results from a national survey of UPIs in Germany. On the one hand these results show that UPI's organization differs in many aspects: size, age, planned time horizon, and total financial volume. On the other hand similarities could be identified, such as: UPIs offer consultancy, training, mentoring and coaching services, set requirements for accessing the UPI program, have common target groups, and are integrated in external as well as internal networks. In addition, a case study of the UPI 'Gruendungslabor' is presented before motivating possible fields for future research.
urn:nbn:de:101:1-200911172029
Keywords: 330; Forschungskooperation; Unternehmensgründung; Wirtschaftsförderung; Business Angels; Deutschland